Existence and non-existence of positive solutions for integral boundary value problems of high-order fractional differential equations with generalised p-Laplacian operator. Issue 1 (2017) - Li, Bingxian; Sun, Shurong; Chen, Guanwei
In this paper, we investigate the non-linear integral boundary value problem of fractional differential equations with generalised p-Laplacian operator. By means of the monotone iteration method, we obtain the existence of positive solutions and establish the iterative sequence for approximating the solutions. Moreover, the non-existence of positive solution is also considered. An example is given to show the applicability of our main results.